Characterization of putative RKD homologous gene with microspore embryogenesis in the local pigmented rice cultivar segreng - Nurbaiti, S.; Indrianto, A.; Purwestri, Y. A.; Daryono, B. S.; Semiarti, E. (the official publication of the society called the SABRAO Journal of Breeding and Genetics, 2021)
The local pigmented rice cultivar Segreng from Yogyakarta, Indonesia, has the potential to be a staple food, as well as medicine, because it contains a red pigment and high amounts of Î²-carotene. Compared with conventional methods, microspore embryogenesis is a shorter way for producing double haploid plants, which are important in plant breeding. The study of the mechanism related to this type of embryogenesis is required to increase its efficiency. RKD genes containing the RWPXRK motif (RWPRK) domain protein play an important role in the initiation of embryogenesis at the very early stage in zygotic and somatic embryogenesis. Exploring the involvement of the RKD gene in microspore embryogenesis induction will be very helpful. This study, we isolated the putative RKD homologous gene of the local pigmented rice cv. Segreng and analyzed its expression at the early induction stage of microspore embryogenesis. The partial sequence of the RKD homologue was isolated from this cultivar and found to consist of 563 bp encoding 75 amino acid sequences. Bioinformatics analysis by using BLASTP search showed that the putative RKD protein had high similarity with the RKD1 protein of Oryza sativa subsp. japonica cv. Nipponbare and the hypothetical protein of O. sativa subsp. indica that contained the RWPRK motif. Protein analysis showed the presence of conserved amino acid sequences in N-terminal region of Oryza sativa RKD proteins. The fold-change in the relative expression level in RKD compared with that in the control was elevated from the first until the third day and decreased on the fourth day. Â© Society for the Advancement of Breeding Research in Asia and Oceania (SABRAO) 2021.